Carotenoid as a potential antioxidant marker for schizophrenia - Chow, T.J; Loh, H.C (Universiti Kebangsaan Malaysia, 2012)
Free radicals are results of aerobic activities and can damage cells when present in excess by causing oxidative stress. Antioxidants efficiently quench free radicals to counteract oxidative stress. Carotenoids are antioxidants that have detectable natural colorant which can be measured as indicator of antioxidant level in human. The aim of this study is to investigate possible association of carotenoid antioxidant levels in schizophrenia. A total of 524 patients with schizophrenia from Hospital Bahagia Ulu Kinta, Malaysia and 391 healthy controls were recruited. Subjects’ skin carotenoid levels were measured through a non-invasive approach using Raman spectroscopy. Patients with schizophrenia showed significant (p < 0.01) lower carotenoid level compared to healthy controls. Factors such as gender, age, subtypes, antipsychotic drug treatments, and duration of illness did not differ significantly among patients. It is concluded that patient with schizophrenia have low levels of carotenoid antioxidants and is suggested to experience higher level of oxidative stress compared to healthy individuals.